2008
DOI: 10.1002/em.20365
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genotoxicity in rats treated with the antidiabetic agent, pioglitazone

Abstract: Pioglitazone (PIO), a member of the thiazolidinedione class of antidiabetic agents, specifically targets insulin resistance. Drugs of this class act as ligands for the gamma subtype of the peroxisome proliferator-activated receptor. Although troglitazone, another drug in this class, displayed unacceptable hepatotoxicity, PIO was approved for human use by the U.S. Food and Drug Administration. To our knowledge, there are no published reports on the genotoxicity of PIO; however, the package insert indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…This is consistent with the previous studies, for example Bedir et al indicated that pioglitazone induces DNA damage in a dose-dependent manner in both liver cells and peripheral whole blood lymphocytes of rats [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the previous studies, for example Bedir et al indicated that pioglitazone induces DNA damage in a dose-dependent manner in both liver cells and peripheral whole blood lymphocytes of rats [9].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, pioglitazone was shown to reduce blood pressure, atherogenic dyslipidemia, microalbuminuria and visceral obesity [8]. Two studies showed that, pioglitazone can induce DNA damage to liver and blood cells [9]. This DNA damage is suggested to be the result of the generation of free radicals due to increased oxidative stress, resulting from the uncoupled cellular environment and cytochrome enzymes mediated oxidation reaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite sporadic contradictory studies [20, 55], PIO has been reported to attenuate liver injury via recovering hepatic oxidant/antioxidant balance in several animal models, as it succeeded in repairing hepatic DNA damaged due to high fat diet in mice [56], abolishing hepatic oxidative stress in alloxan-induced diabetic rabbit [57], preventing lipopolysaccharide-induced liver injury [58], and recovering liver after ischemia/reperfusion in rats [23]. In humans, PIO was demonstrated to improve hepatic functional parameters in nonalcoholic fatty liver patients [59] and in nondiabetic patients suffering from metabolic syndrome [60].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement in the oxidative stress due to generation of free radicals from the mitochondrial and/or extra mitochondrial sources was considered as the possible reason for the PIO mediated nuclear damage (Bedir et al 2008). However, several studies in the past have reported that TZDs posses potent anti-oxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reveals that PIO administration for 2 weeks (10–40 mg/kg/day) has enhanced the DNA damage in rat hepatocytes and blood lymphocytes (Bedir et al 2008). Similarly, in another study, RSG has shown increased nuclear damage in rat hepatocytes when it was tested daily (0.5–2.0 mg/kg) for two weeks (Bedir et al 2006).…”
Section: Introductionmentioning
confidence: 99%